2020
DOI: 10.1073/pnas.1919390117
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic resistance by high-level intrinsic suppression of a frameshift mutation in an essential gene

Abstract: A fundamental feature of life is that ribosomes read the genetic code in messenger RNA (mRNA) as triplets of nucleotides in a single reading frame. Mutations that shift the reading frame generally cause gene inactivation and in essential genes cause loss of viability. Here we report and characterize a +1-nt frameshift mutation, centrally located in rpoB, an essential gene encoding the beta-subunit of RNA polymerase. Mutant Escherichia coli carrying this mutation are viable and highly resistant to rifampicin. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…It has been postulated that both translational frameshifting and the propensity of the DNA replication errors at these sequences aid the cells in antigenic variation and evasion of the host immune system. In M. tuberculosis, some rifampicinresistant strains contain an insertion mutation in rpoB, the b subunit of RNA polymerase (110). This insertion is suppressed by a subsequent translational 11 frameshift that leads to a 3-amino acid change in RpoB, resulting in high levels of rifampicin resistance.…”
Section: Proteome Regulation Through Frameshiftingmentioning
confidence: 99%
“…It has been postulated that both translational frameshifting and the propensity of the DNA replication errors at these sequences aid the cells in antigenic variation and evasion of the host immune system. In M. tuberculosis, some rifampicinresistant strains contain an insertion mutation in rpoB, the b subunit of RNA polymerase (110). This insertion is suppressed by a subsequent translational 11 frameshift that leads to a 3-amino acid change in RpoB, resulting in high levels of rifampicin resistance.…”
Section: Proteome Regulation Through Frameshiftingmentioning
confidence: 99%
“…By coupling genetic and proteomic approaches, it was recently shown that frameshifting of the rpoB gene is a mechanism used by pathogenic mycobacteria to generate resistance to antibiotics [ 142 ]. Importantly, LC/MS/MS was applied to demonstrate low levels of frameshift suppression of rpoB mutations, indicating that sometimes, what is encoded in the genome does not necessarily predict the resulting proteome [ 142 ]. The decoupling of the proteome from the genome underscores the necessity of combining approaches that alter the genome and measure the proteome.…”
Section: The Genetic Proteome and Antibiotic Susceptibility And Resismentioning
confidence: 99%
“…It is noteworthy that most of the mutations occurred in membrane proteins whose involvement hasn't been highlighted in this work even though it's logical to assume that the cell membrane would be the first barrier to exogenous isobutanol and its toxicity. The real problem is our incomplete knowledge of the linkages between genome and transcriptome and hence our inability to predict phenotype from changes in the genome sequence 55 .…”
Section: S No Locus_tagmentioning
confidence: 99%